2002
DOI: 10.1515/cclm.2002.100
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bikunin Determination Provides Insight into Proteinase/Proteinase Inhibitor Imbalance in Patients with Inflammatory Diseases

Abstract: Bikunin (BK) is a Kunitz-type proteinase inhibitor responsible for most of the antitryptic activity of urine and so is known as the urinary trypsin inhibitor. As its excretion increases in inflammatory conditions, it is often considered to be a positive acute phase protein (APP). However, the gene for BK is downregulated in inflammation. In human plasma the major part of BK is covalently linked through a glycosaminoglycan chain to one or two homologous peptide heavy chains, thus forming high molecular weight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
0
24
1
2
Order By: Relevance
“…Bikunin excretion increases in inflammatory conditions and is often considered to be a positive acute phase protein. It was demonstrated that during inflammatory diseases, concentrations of serum high molecular weight bikunin products are dependent on their rate of utilization as well as on regulation of their biosynthesis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Bikunin excretion increases in inflammatory conditions and is often considered to be a positive acute phase protein. It was demonstrated that during inflammatory diseases, concentrations of serum high molecular weight bikunin products are dependent on their rate of utilization as well as on regulation of their biosynthesis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins are known to inactivate NE activity and NE degrades the pre-a-/inter-a-trypsin inhibitors, proteinase inhibitors, that release UTI [14,15]. UTI has been reported to be a positive acute phase protein whose concentration in serum and excretion in urine is increased in proportion to the invasiveness of the various diseases and the activation of neutrophils [17,18]. Previous study showed that both NE and UTI concentrations in BAL fluid of acute respiratory distress syndrome are significantly elevated, but only UTI concentration is significantly high in the serum [20].…”
Section: Discussionmentioning
confidence: 99%
“…Assay of urinary trypsin inhibitor, neutrophil elastase, a 1 -antitrypsin, tissue inhibitor of metalloproteinase-1 and matrix metalloproteinase-2 Serum UTI was determined by sandwich-type one-step enzyme immunoassay using polyclonal antibodies to human trypsin inhibitor [14,17,18] and a human assay kit (Mochida Pharmaceutical Co. Ltd., Tokyo, Japan). The ELISA procedure makes it possible to specifically measure UTI by trapping pre-a-/inter-a-inhibitors in solid phase with a treatment of perchloric acid.…”
Section: Controlsmentioning
confidence: 99%
“…Тяжесть заболевания 0/3/10/4 * 2/4/2/3/2 ** *** (рисунок). Показано, что альфа-1-микроглобулин ингибирует иммунные функции лейкоцитов in vitro и его распределение связывают с защитной и противовоспалительной ролью in vivo [10], а репрессия бикунина характерна для воспаления [11]. Эти данные позволяют предположить, что острое воспаление, сопровождающее как ХОБЛ, так и пневмонию, может вызывать снижение уровня экспрессии предшественника альфа-1-микроглобулина/бикунина.…”
unclassified